The psychology of exceptional children - Garrison, Karl C. (Karl Claudius), 1900-1980; Force, Dewey George, 1921- (New York : Ronald Press Co., 1959)
The purpose of this book is to bring together in brief and systematic form much of the pertinent knowledge of exceptional children which bears upon their education. Because the book is designed primarily as a textbook for students enrolled in teacher-education institutions, and as a source of reference for teachers in service, emphasis is placed on the contribution which the regular classroom teacher can make to the education and welfare of the exceptional child"
Part 1. Children : human resources -- part 2. Mental deviates -- part 3. Physical disability -- part 4. Neurological impairments and health problems -- part 5. Emotional and social maladjustments.
Includes bibliographical references and indexes.
Keywords: Exceptional children; Ability; Educational psychology; Psychology, Pathological; Child, Exceptional; Aptitude; Psychology, Educational; Psychopathology